Prioritizing STEAM Education from the Start: The Path to Inclusive and Sustainable STEAM Education - Nyaaba, Matthew; Akanzire, Bismark Nyaaba; Mohammed, Salamatu Haruna (International Journal of STEM Education for Sustainability, 2024)
This study highlights the significance of prioritizing STEAM (Science, Technology, Engineering, Arts, and Mathematics) education from the early stages of learning as a crucial step towards achieving inclusive and sustainable STEAM education. The study adopted a critical discourse analysis (CDA) and an allegory method entitled 'The Ancient Multi-Story Building'. The CDA involved studies, reports, and news on STEM-related and STEM initiatives in Ghana. The findings revealed a substantial gap in early childhood and primary education STEAM initiatives, largely due to prevailing misconceptions about these levels of education. The allegory of the 'Ancient Multi-Story Building' further explains the adverse impact of this gap by metaphorizing the flawed approach of initiating and investing in upper-level STEAM education while neglecting the lower-level years, much like a village constructing a multi-story building focusing on the higher floors without solidifying its base; obviously, the results will be disastrous. Similarly, the findings show that previous STEM-related initiatives in Ghana focusing on upper-level education have often been inclusively ineffective. The allegory further points out that the few students who thrive in these lopsided STEM-related pathways are typically those from affluent backgrounds with the necessary support. The study indicated that starting STEAM education in the early years of education has the potential to promote gender equity, cultivate critical thinking skills, and develop a positive attitude towards STEAM subjects among all young learners. This study, therefore, lays the groundwork to propose a strategic framework for early childhood and primary STEAM education in Ghana and other similar contexts.